2019
DOI: 10.1093/cid/ciz430
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Immunoglobulin A Against a Sporozoite Antigen at 12 Months Is Associated With Delayed Time to Subsequent Cryptosporidiosis in Urban Bangladesh: A Prospective Cohort Study

Abstract: In this prospective cohort study of Bangladeshi children, greater fecal immunoglobulin A, but not plasma immunoglobulin G, directed against the Cryptosporidium sporozoite-expressed antigen Cp23 at 12 months of age was associated with delayed time to subsequent cryptosporidiosis. This finding suggests a protective role for mucosal antibody-mediated immunity in naturally exposed children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…Protection for Cryptosporidium was larger against diarrhea (70% vs 25%) and smaller against subclinical infection (20% vs 50+%) compared with a study in India [ 32 ]. The evidence for natural immunity to Cryptosporidium is supported by protection observed among adults with pre-existing serum antibodies [ 33 ] and delayed cryptosporidiosis among children with higher levels of anti- Cryptosporidium fecal immunoglobulin A (IgA) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Protection for Cryptosporidium was larger against diarrhea (70% vs 25%) and smaller against subclinical infection (20% vs 50+%) compared with a study in India [ 32 ]. The evidence for natural immunity to Cryptosporidium is supported by protection observed among adults with pre-existing serum antibodies [ 33 ] and delayed cryptosporidiosis among children with higher levels of anti- Cryptosporidium fecal immunoglobulin A (IgA) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…(Slope: -0.294 ± 0.05; R squared value: 0.08; Significance p < 0.0001). C) Relationship of all-cause diarrhea with HAZ at 3 years of age (p = NS).Mucosal IgA against the sporozoite Cp23 protein was associated with protection from growth falteringIn previous work it was shown in this cohort that a high level (> mean value) of fecal anti-Cp23IgA at one year of age was associated with an increased resistance to cryptosporidiosis through age three[14,20]. Here we additionally discovered that children with high levels (upper 50 th percentile) of fecal anti-Cp23 IgA at one year of age were protected from growth faltering through year 3(Fig 6).…”
mentioning
confidence: 79%
“…infections [0 -3 years] (both diarrhea and sub-clinical) ( Table 2, Fig S5 & 6). The association between cryptosporidiosis and HAZ score at three years was examined by multiple regression in order to account for the effect of the confounding variables previously identified (Table 3) [13,21]. infections was unaffected by whether the event was a sub-clinical infection or diarrheal disease ( Fig S7).…”
Section: Cryptosporidium and Growth Falteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with high levels of fecal anti-Cp23 IgA were regarded as being previously exposed to the Cryptosporidium parasite even if the parasite had been missed during surveillance for subclinical infections. In previous work it was shown that even if Cryptosporidium DNA had not been identified high levels (> mean value) of fecal anti-Cp23 IgA at one year of age was associated with an increased resistance to cryptosporidiosis through age three [14,20]. In children with high fecal anti-Cp23 IgA there was an increase in the number of days until a child was reinfected and a subsequent decrease in the proportion of children in this group reinfected during years 2-3 (in children with high fecal anti-Cp23 IgA 77.8% were reinfected versus 92.2%) Here we additionally discovered that children with high levels (upper 50 th percentile) of fecal anti-Cp23 IgA at one year of age were protected from growth faltering through year 3…”
Section: Mucosal Iga Against the Sporozoite Cp23 Protein Was Associated With Protection From Growth Falteringmentioning
confidence: 99%